Deciphering the serological response to syphilis treatment in men living with HIV. (15th November 2020) - Ren, Melody; Szadkowski, Leah; Walmsley, Sharon L.
Abstract : Objective: To examine syphilis serology after treatment in people living with HIV. No unanimous guidelines exist in the era of increasing coinfection. Design: Retrospective review using a tertiary care clinic in Toronto from 2000 to 2017. Methods: The 2015 Centers for Diseases Control and Prevention syphilis guidelines were used to define an adequate serologic response. Cumulative distribution estimates and proportional hazards models accounting for interval censoring estimated the time to serologic response and seroreversion. Multistate models were used to investigate extended periods of serofast serology. Results: A total of 171 patients with syphilis met our inclusion criteria (16 primary, 53 secondary, 26 early latent, 46 late latent, 30 neurosyphilis). Serologic response was achieved by 12 months for 65 (94%) patients and by 12–18 months for four (6%) patients with primary/secondary syphilis. For latent and neurosyphilis, 94 (92%) achieved serologic response by 24 months and one (1%) at 24.1 months. 84 (49%) patients achieved seroreversion with a median (95% confidence interval) time of 2 (1.44, 2.68) years. Latent syphilis was associated with a lower likelihood of achieving serologic response [hazard ratio (HR) = 0.52, P  = 0.05] and seroreversion (HR = 0.27, P  < 0.001) compared with primary/secondary syphilis. The probability of moving from a new infection state to a serofast state within 1 year was high (0.65) but the 1-year probability of transitioning from a serofast state to seroreversion was low (0.27). Conclusion: The majority of people living with HIV infected with syphilis will achieve an adequate serologic response as per the Centers for Diseases Control and Prevention guidelines. Seroreversion was observed in about half but can take years to occur.